2022
DOI: 10.1136/ihj-2021-000092
|View full text |Cite
|
Sign up to set email alerts
|

Equity in healthcare access and service coverage for older people: a scoping review of the conceptual literature

Abstract: There is currently no global review of the conceptual literature on the equity of healthcare coverage (including access) for older people. It is important to understand the factors affecting access to health and social care for this group, so that policy and service actions can be taken to reduce potential inequities. A scoping review of published and grey literature was conducted with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Specifically, stakeholders shared strategies that would increase the accessibility of the materials as well as ways to address privacy concerns within the modules. Accessibility of training materials and resources to promote competence of telehealth is critical to reducing disparities to health service access experienced by this population ( Carroll et al, 2022 ) and improving client experiences as part of the Quadruple Aim ( Bodenheimer & Sinsky, 2014 ). Novel findings from this study also showed that online training materials, when adapted to meet older adults’ needs, may be efficacious in increasing their perceived competence and confidence to use telehealth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, stakeholders shared strategies that would increase the accessibility of the materials as well as ways to address privacy concerns within the modules. Accessibility of training materials and resources to promote competence of telehealth is critical to reducing disparities to health service access experienced by this population ( Carroll et al, 2022 ) and improving client experiences as part of the Quadruple Aim ( Bodenheimer & Sinsky, 2014 ). Novel findings from this study also showed that online training materials, when adapted to meet older adults’ needs, may be efficacious in increasing their perceived competence and confidence to use telehealth.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these barriers, older adults express a willingness to adopt telehealth to access services that would facilitate independent living ( Edwards et al, 2014 ; Qin, 2022 ; Vaportzis et al, 2017 ). Targeted and accessible training is critical for adoption among this population ( Carroll et al, 2022 ).…”
mentioning
confidence: 99%
“…The availability and accessibility of healthcare services may not be sufficient to encourage older people to access them. Moreover, older people should not be treated as a homogeneous group [ 39 ], as factors that act as enablers or barriers for a particular individual may not apply to other older persons.…”
Section: Discussionmentioning
confidence: 99%
“…Access to services under COVID-19 restrictions matters because older people worldwide tend to have disadvantaged access to health and social care services even prior to the pandemic [10]. Disadvantage relates to the ways that health and social care services operate in a way that privileges younger populations, for example, by focusing on curative, rather than recovery and long-term, care [11].…”
Section: Introductionmentioning
confidence: 99%